No-Reflow Phenomenon and Endothelial Glycocalyx of Microcirculation - Alexander V. Maksimenko; Askar D. Turashev (Biochemistry Research International)
The progress in reperfusion therapy dictated the necessity for developing new tools and procedures for adjacent/additional therapy of acute cardiovascular disorders. The adjacent therapy is targeted on the damage of the microcirculation, leading to the unfavorable prognosis for the patients. The no-reflow phenomenon holds special place in the multifactorial etiology of the microcirculation disorders, offering a new challenge in treating the patients associated with ST-segment elevation on ECG at myocardial infarction. One of the numerous causes of no-reflow, the influence of the endothelial glycocalyx of the microcirculation, is analyzed. The results obtained in the studies of the endothelial glycocalyx ultrastructure are generalized, the effect that the fragments of the glycocalyx glycosaminoglycans have on the function of the vascular wall is demonstrated. The trends in searching for correlations between the thickness of the capillary glycocalyx and the cardiovascular disease risk are noted.